Design and application of a Health Insurance Portability and Accountability Act-compliant privacy framework for pervasive healthcare. (30th April 2008) - Malladi, Srilaxmi; Varshney, Upkar
With an increasing emphasis on pervasive healthcare services, providing a high degree of privacy to patients is becoming a major challenge due to: (a) an increased number of avenues, such as device, access points, switches and database; (b) more threats to privacy then ever before and (c) a higher expectation from society due to the sensitive and personal nature of medical and health information. In this paper, we present a framework for privacy in pervasive healthcare. Various applications and scenarios have been identified, details of the framework are presented and its applications to representative pervasive healthcare applications.